2021
DOI: 10.1117/1.jbo.26.12.126002
|View full text |Cite
|
Sign up to set email alerts
|

3D retinal imaging and measurement using light field technology

Abstract: . Significance: Light-field fundus photography has the potential to be a new milestone in ophthalmology. Up-to-date publications show only unsatisfactory image quality, preventing the use of depth measurements. We show that good image quality and, consequently, reliable depth measurements are possible, and we investigate the current challenges of this novel technology. Aim: We investigated whether light field (LF) imaging of the retina provides depth information,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 32 publications
0
10
2
Order By: Relevance
“…Further, a study by Arcadu et al 37 showed that DL could not only identify fundus color photographs with macular thickness >250 µm but also had the potential to predict specific values of fovea macular thickness from fundus photographs. Regarding hardware, Schramm et al 38 achieved 3-dimensional (3D) retinal imaging based on light field technology, and they successfully estimated the depth of the retina in one-shot imaging with an accuracy comparable to OCT measurement. This technology, combined with AI, is expected to improve the accuracy of DME screening further.…”
Section: Review Methodologymentioning
confidence: 99%
“…Further, a study by Arcadu et al 37 showed that DL could not only identify fundus color photographs with macular thickness >250 µm but also had the potential to predict specific values of fovea macular thickness from fundus photographs. Regarding hardware, Schramm et al 38 achieved 3-dimensional (3D) retinal imaging based on light field technology, and they successfully estimated the depth of the retina in one-shot imaging with an accuracy comparable to OCT measurement. This technology, combined with AI, is expected to improve the accuracy of DME screening further.…”
Section: Review Methodologymentioning
confidence: 99%
“…In an effort to advance the state of the art in glaucoma diagnostics with none of the aforementioned limitations, a new method was developed that generates 3D images of the fundus with only one photographic shot via the use of a fundus camera in combination with light field (LF) technology. 24 27 Using this method, the entire LF is recorded with a microlens array that facilitates the reconstruction of depth information and provides a representation of the surface of the papilla. 28 A subsequent 3D analysis is also possible.…”
Section: Introductionmentioning
confidence: 99%
“… 28 A subsequent 3D analysis is also possible. A technical setup that could be used for papilla imaging was presented by Schramm et al 24 In this publication, the authors documented a method for LF imaging of the ONH and showed that relevant depths could be quantified in units of virtual mm (v-mm). However, calibration is needed to compare these results with data from other imaging systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations